Caterpillar - parasitoid food webs in New Guinea rainforest - Hrček, Jan (Jihočeská univerzita, 2012)
The thesis establishes baseline ecological parameters (parasitism rate, host specificity, and food web structure) for tropical external folivore - parasitoid food webs and finds the parasitoids strongly host specific. Further, it presents a new method for molecular detection of herbivore - parasitoid relationships, and describes some of the studied species to ensure long-term value of the ecological data.
Caterpillar - parasitoid food webs in New Guinea rainforest